2008
DOI: 10.1159/000115954
|View full text |Cite
|
Sign up to set email alerts
|

Religious Delusions: Finding Meanings in Psychosis

Abstract: Background: Religious delusions have been reported with varying prevalence from cultures around the world. Their contents, context and significance vary according to cultural and economic mores. In this review we discuss the potential relationship between religious delusions and aspects of culture, in particular religious symbols. We suggest that religious rituals and expectations of the family play a major role in the genesis and maintenance of delusions. We consider the roles of religious signifiers in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 73 publications
1
19
1
5
Order By: Relevance
“…People with religious delusions also reported more internal evidence for their delusions (anomalous experiences or mood changes), and were very likely to have an accompanying grandiose delusion. In contrast to findings in the literature [1, 3, 4, 1319], they had lower levels of negative symptoms, with no differences in their degree of delusional conviction or in the likelihood of them engaging in treatment. Levels of affective disturbance were similar in RD compared to other delusions, and reasoning biases were, if anything, less pronounced in the religious delusions group, as people with religious delusions were more likely to be able to identify an alternative to their delusion.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…People with religious delusions also reported more internal evidence for their delusions (anomalous experiences or mood changes), and were very likely to have an accompanying grandiose delusion. In contrast to findings in the literature [1, 3, 4, 1319], they had lower levels of negative symptoms, with no differences in their degree of delusional conviction or in the likelihood of them engaging in treatment. Levels of affective disturbance were similar in RD compared to other delusions, and reasoning biases were, if anything, less pronounced in the religious delusions group, as people with religious delusions were more likely to be able to identify an alternative to their delusion.…”
Section: Discussioncontrasting
confidence: 97%
“…Levels of disability, distress and conviction have all been reported to be higher in people with religious delusions compared to other types of delusions [1, 3, 4, 1315]. Religious delusions are also associated with poor engagement, low satisfaction with services and with treatment, and longer duration of untreated psychosis [12, 1619].…”
Section: Introductionmentioning
confidence: 99%
“…Our study provided support to the theory that the culture and expectations in a society influence the nature of the delusions that are formed and maintained in it 29. Understanding the psychosocial meaning of specific delusions in patients with psychosis is an interesting topic for cultural psychiatrists, as well as being clinically significant for clinicians working with this population.…”
Section: Discussionsupporting
confidence: 73%
“…Greenberg (2009) reports a case of an Ultra-Orthodox Jewish woman, born in Israel, with parents from north Africa, who, using similar kabalistic ideas which are also prevalent among Sephardic Jews, reported that she is the Shekhinah (the Divine Presence), and her real husband is God. Religious delusions have been viewed in terms of the relief of communal anxieties, fulfilment of social roles and the development of new religious movements (Bhavsar & Bhugra, 2008). Those delusions of being the Shekhinah and/or the Queen Messiah could be the manifestation of a desire by some women across the strictly Orthodox Jewish communities for more direct integration into the mystical redemptive process.…”
Section: Analysis Of Miriam's Beliefs and Delusionsmentioning
confidence: 99%